Effects of Pre–Cardiopulmonary Bypass Administration of Dexmedetomidine on Cardiac Injuries and the Inflammatory Response in Valve Replacement Surgery With a Sevoflurane Postconditioning Protocol: A Pilot Study - Zhou, Hongmei (J Cardiovasc Pharmacol, 2019)
BACKGROUND: Preventing myocardial ischemia–reperfusion injury in on-pump cardiac surgeries remains an enormous challenge. Sevoflurane postconditioning has been effective at overcoming this challenge by modulating inflammatory mediators and ameliorating antioxidative stress. Dexmedetomidine (DEX) is a commonly used medication for cardiac patients with organ-protective properties that lead to positive outcomes. Whether DEX also has cardiac-protective properties and the associated mechanism in sevoflurane postconditioning–based valve replacement surgeries are unknown. OBJECTIVE: This study was conducted to observe the effect of DEX administration before cardiopulmonary bypass (CPB) on myocardial injury, oxidative stress, and inflammatory response indicators in the peripheral blood. METHODS: Twenty-eight eligible cardiac patients who underwent valve replacement surgery with standard sevoflurane postconditioning were included in the study. The patients were randomly divided into a DEX group and a non-DEX group according to whether DEX (0.5-µg/kg overload dose for 10 minutes and a 0.5-μg/kg/h maintenance dose) or saline was administered from induction to the beginning of CPB. The primary outcome was the cardiac troponin I concentration (cTnI) in the blood 24 hours after CPB. The levels of malondialdehyde (MDA), superoxide dismutase, tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-8 (IL-8) were also measured. RESULTS: The mean cTnI at 24 hours after CPB was clearly decreased in the DEX group compared with that in the non-DEX group (4.16 ± 1.58 vs. 6.90 ± 3.73, P < 0.05). TNF-α levels were lower in the DEX group after CPB (T1–T5), with a significant difference found at 1–6 hours after CPB (1 hour, 19.03 vs. 28.09; 6 hours, 20.74 vs. 30.94, P < 0.05). The IL-6 and IL-8 concentrations in the DEX group were dramatically increased at 6 hours after CPB (P < 0.05). The MDA content and superoxide dismutase activity were comparable between the 2 groups. A lower proportion of anemia cases were noted after CPB in the DEX group than in the non-DEX group (non-DEX, 10% vs. DEX, 5%, P < 0.05). CONCLUSIONS: In valve replacement surgery with sevoflurane postconditioning, pre-CPB administration of DEX can reduce the cTnI level at 24 hours after CPB and brings synergic benefits of the inflammatory response.